2022
DOI: 10.3389/fpubh.2022.1017271
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and arteriosclerotic cardiovascular disease risk and cause-specific and all-cause mortality: Data from the 2005–2018 National Health and Nutrition Examination Survey

Abstract: BackgroundMorbidity and mortality of arteriosclerotic cardiovascular disease (ASCVD) varied according to socioeconomic status (SES), and evidence on the association between SES and ASCVD risk, and cause-specific and all-cause mortality was nevertheless lacking in large-scale or population-based studies.MethodsA multicycle cross-sectional design and mortality linkage study was conducted using data from Continuous National Health and Nutrition Examination Survey (NHANES) in the United States, including public us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These studies emphasize that SDOH are indeed fundamental drivers of poor health. For example, adjustment for lifestyle factors assessed by life’s simple 7 score, now life’s essential 8, only slightly attenuated the association between SES and ASCVD risk in another study of NHANES participants ( Shen et al, 2022 ). In fact, some studies have suggested that even at best, traditional CVD risk factors can account for only 15–30 percent of the relationship between SES with CVD mortality ( Marmot et al, 1984 , Bhatnagar, 2017 , Henderson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies emphasize that SDOH are indeed fundamental drivers of poor health. For example, adjustment for lifestyle factors assessed by life’s simple 7 score, now life’s essential 8, only slightly attenuated the association between SES and ASCVD risk in another study of NHANES participants ( Shen et al, 2022 ). In fact, some studies have suggested that even at best, traditional CVD risk factors can account for only 15–30 percent of the relationship between SES with CVD mortality ( Marmot et al, 1984 , Bhatnagar, 2017 , Henderson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between SES and cardiovascular health (CVH) outcomes has been well studied in various racial/ethnic groups ( Lloyd-Jones et al, 2009 , Brewer et al, 2018 , Gasevic et al, 2015 , Wenger et al, 2022 , Bello et al, 2022 ), fewer studies have evaluated the relationship between SDOH and ASCVD risk among ethnic/racial minorities within the US ( Shen et al, 2022 ). Therefore, the goal of our study was to assess the relationship between SES and ASCVD risk and determine whether these associations were modified by sex and race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Three weighted Cox proportional hazards regression models were used to estimate the associations of cancer and cancer types with the all-cause and cardiovascular-related mortality probabilities after controlling for possible confounding factors. Accumulating evidence suggests disparities in risk factors of CVD in the general population, depending on age, sex, ethnicity, marital status, educational level, income, and the AHA's Life's Simple 7 cardiovascular health score [18][19][20][21][22][23][24][25][26][27][28][29]. Therefore, the multivariable model included the following confounders based on previously published studies: age (<50 or ≥50 years), sex (male or female), ethnicity (White or Non-White), marital status (living with a spouse/partner or living without a spouse/partner), PIR [low (<1.3), middle (1.3-3.5), or high (≥3.5) income], educational level (under 9th grade, 9-11th grade, high school graduate, some college or AA degree, or college graduate or above), and the AHA's Life's Simple 7 cardiovascular health score (continuous).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that less ideal CVH is associated with depression, and interventions targeting diet, physical activity, and sleep may ameliorate depressive symptoms [ 6 , 7 ]. Meanwhile, individuals with low SES are often exposed to unhealthy lifestyles, which in turn significantly increase their susceptibility to cardiovascular disease [ 8 ]. However, important gaps remain.…”
Section: Introductionmentioning
confidence: 99%